Improving Effective Screening and Management of Obesity in an Urgent Care Clinic - Heather Cynowa; Stephanie Hodges; Christy Swinson (Journal of Obesity Management, 2023)
Background Nearly 40% of the adult population in the United States are considered obese by current standards, which equates to approximately 93 million people. Obesity is a chronic disease that is linked to more than 40 other diseases, including hypertension, heart disease, stroke, diabetes, and at least 13 distinct types of cancers. The direct and indirect costs of obesity have been estimated at up to 210 billion annually. Local Problem In Cumberland County, North Carolina, 34% of the adult population was considered obese. The aim of this quality improvement study was to increase effective care (screening, patient engagement, and referral to treatment) in adult patients with a BMI greater than 30 kg/m2 to 75% within 90 days. Methods A rapid cycle plan-do-study-act framework was used to evaluate four focus areas concurrently over 8 weeks with a small test of change completed in each 2-week cycle. Interventions An expanded screening with a checklist, shared decision-making tools (SDMTs), and a referral to treatment checklist were implemented. Activities from the team engagement plan were initiated. Results The effective care of patients increased by 42 percentage points while engaging both the patients and the staff. Conclusions Utilizing standardized communication, SDMTs, checklists, and management plans improved effective care while motivating and enabling patients to take control of their care and make sustainable lifestyle changes that enhance overall health.
Keywords: Quality improvement